Dacryodes edulis, a neglected non-timber forest species for the agroforestry systems of West and Central Africa - Sonwa, D.J.; Okafor, J.C.; Buyungu, P.M.; Weise, Stephan F.; Tchatat, M.; Adesina, A.A.; Nkongmeneck, B.A.; Ndoye, O.; Endamana, D. (2002)
Dacryodes edulis, or safou, is a fruit tree native to Central Africa and the Gulf of Guinea region. It is usually present in agroforestry systems in the region, particularly in homegardens and cocoa and coffee agroforests. It plays an important role in household consumption and the surplus is sold on the rural and urban market. A lack of attention by research and extension services means that there is neither scientific knowledge nor official recommendations for its management in agroforestry systems. The attemp to introduce it into forest fallows in Cote d'Ivoire is a good example of industrial involvement in the development of agroforestry and the expansion of tree production in West Africa. Drawing on experience from Cameroon, Nigeria and Cote d'Ivoire, this paper presents indigenous management techniques and emerging opportunities to promote safou in West and Central African agroforestry systems for food security, income generation and rehabilitation of the environment.